Communicating emotion at work - Waldron, Vincent R. (Cambridge : Polity, 2012)
'The book chronicles the rich emotional experiences of employees drawn from a broad cross-section of industries and occupations. It takes a decidedly positive approach, rocognizing that emotional communication is a vital and creative response to the challenges of life ini complex organizations. The text introduces readers to the engaging and cross-disciplinary body of research that has emerged around organizational emotion. At the same time, each chapter is steeped in real-life emotional narratives, concrete examples, and the contemporary trends that are changing the emotional tenor of work.'--BOOK JACKET.
Includes bibliographical references and index.
Keywords: Communication in management -- Psychological aspects; Emotions